How Land Title Affects Child Labor? - Serpa Barros de Moura, Mauricio Jose; da Silveira Bueno, Rodrigo De Losso; Leony, Larissa (2012)
Secure property rights are considered a key determinant of economic development. However, evaluation of the causal effects of land titling is a difficult task. Since 2004, the Brazilian government, through a program called "Papel Passado," has issued titles to more than 85,000 families and has the goal to reach 750,000. Another topic in public policy that is crucial for developing economies is child labor force participation. In Brazil, about 5.4 million children and teenagers between 5 and 17 years old are working full time. This paper examines the direct impact of securing a property title on child labor force participation. In order to isolate the causal role of ownership security, this study uses a comparison between two close and similar communities in the City of Osasco case (a town with 650,000 people in the São Paulo metropolitan area). The key point of this case is that some units participate in the program and others do not. One of them, Jardim Canaã, received land titles in 2007; the other, Jardim DR, given fiscal constraints, will not be part of the program until 2012, and for that reason became the control group. Estimates, generated using the difference-in-difference econometric technique suggest that titling results in a substantial decrease in child labor force participation for the families that received the title compared with the others. These findings are relevant for future policy tools for dealing with informality and how it affects economic growth.